683 Cor in memoria posterorum: role of familial screening in sudden death syndrome. (8th December 2021) - Chiti, Chiara; Parisi, Vanda; Graziosi, Maddalena; Biagini, Elena
Abstract: A 14-year-old boy suddenly died during a school lesson. His familial history was negative for sudden cardiac death and no comorbidities were reported. As part of Emilia Romagna regional network for sudden cardiac death, the heart was examined at our Cardiovascular Pathology Unit. The molecular autopsy revealed extensive lymphocytic macrophage left ventricle myocarditis (infero-lateral and anterior wall) in various evolutive stages. Genetic testing with next-generation sequencing was performed on DNA isolated from explanted heart samples (178 candidate genes for channelopathies and cardiomyopathies were analysed) and it showed a frameshift pathological mutation in the filamine C gene (FLNC c.8034delC p. Cys2679fsTer6) which induces protein premature termination. In order to screen family members, we evaluated the father, 53-year-old, asymptomatic and with an unremarkable cardiology history. The ECG showed sinus rhythm, HR 60 b.p.m., normal atrioventricular conduction, QRS fragmentation and negative T waves in the inferior leads. The echocardiogram revealed left ventricle mild dilation (79 mL/m 2 ) with global hypokinesia (EF 45%), while right ventricle was normal for size and kinetics. A cardiac MRI confirmed left ventricular dilation and hypokinesia with diffuse LGE with circumferential mesocardial distribution mainly in the middle-baseline site, which reflected structural damage (fibrosis). The 24-h Holter ECG did not record arrhythmias. The genetic test was then performed and the same FLNC frameshift mutation was identified. We thus suspected familial arrhythmogenic cardiomyopathy involving left ventricle with pathological filamine C mutation and an ICD was recommended. Other family members had no pathological findings. Filamine C mutations are associated with many type of cardiomyopathy. A possible association between some mutated variants and certain subtypes of cardiomyopathy has been highlighted. In particular, the frameshift variant is associated with an increased arrhythmic risk, particularly when dilated forms are considered. Recent studies have identified a correlation with arrhythmogenic cardiomyopathy, although the role of these mutated variants has not yet been fully defined. This clinical case underlines the importance of multidisciplinary approach in cases of sudden cardiac death, consisting of autopsy, genetic and clinical evaluation, in order to identify any forms of familial cardiomyopathy and activate a systematic screening in family members with important prognostic and therapeutic implications. Data about our regional structural network for sudden cardiac death will also be shown.